Islamic Corporate Social Responsibility dan Kinerja Lingkungan Sebagai Determinan Profitabilitas Perbankan Syariah di Indonesia - Esy Nur Aisyah; Riswanti Riswanti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2020)
In carrying out corporate social responsibility, islamic banking must carry out Corporate Social Responsibility in accordance with Islamic law or called Islamic Corporate social Responsibility and pay attention to environmental management, so as to make a good contribution ffrom the community towards the company. This study aims to determine the effect of Islamic Corporate Social Responsibilty and envoromental performance on profitability. The sample used in this study were 11 islamic commercial bank with the study period of 2011-2015. The analytical tool used is multiple regression analysis. The test result show that Islamic Corporate social Responsibility has a significant positive effect on profitability and environmental performance has a significant negative effect on profitability. And based on the result of the determinant test (R square), the ICSR and environmental performance variables are able to explain its effect on profitability by 26%, while the rest is explained by other variables. Keywords: Environmental Performance, Islamic Corporate Social Responsibility, Islamic Banking, Profitability.